Substitution degree and fatty chain length influence on structure and properties of fatty acid cellulose esters. (15th April 2020) - Duchatel-Crépy, Lucie; Joly, Nicolas; Martin, Patrick; Marin, Adeline; Tahon, Jean-Francois; Lefebvre, Jean-Marc; Gaucher, Valérie
Highlights: Homogeneous synthesis of fatty acid cellulose esters (FACEs) with both various substitution degree (DS) and fatty chain lengths. Chemical, thermal, mechanical and WAXS characterizations of FACES. Highlighting structure-property relationships of FACEs according to both DS and fatty chain lengths. Chemical resistance of FACEs to acid and alkali solutions according to concentration and contact time. Abstract: A series of fatty acid cellulose esters (FACEs) with both various degrees of substitution (from DS = 1.7 to 3) and side chain length were obtained by grafting aliphatic acid chlorides (from C10 to C16) onto cellulose backbone, in a homogeneous LiCl/DMAc medium. These materials were characterized by Fourier Transformed InfraRed (FTIR) and Nuclear Magnetic Resonance of Proton ( 1 H NMR) spectroscopies, as well as Wide Angle X-ray Scattering (WAXS), Differential Scanning Calorimetry (DSC), mechanical analyses and chemical resistance to concentrated acid and alkali solutions. Whatever the alkyl chains length and the DS, all samples displayed a layered structure composed of a planar arrangement of parallel cellulosic backbones with fully extended flexible side chains oriented perpendicular to the planar structure without interdigitation. The alkyl chains were able to crystallize as soon as they are long enough. As the DS decreased, the plasticizing effect of the alkyl chains was less pronounced and their ability to crystallize was improved. Regarding the mechanical behavior and the chemical resistance, similar results were observed whatever the DS is.